1995
DOI: 10.1016/0014-5793(95)00077-m
|View full text |Cite
|
Sign up to set email alerts
|

The potent mitogen Pasteurella multocida toxin is highly resistant to proteolysis but becomes susceptible at lysosomal pH

Abstract: The susceptibility of the potent mitogen Pasteurella multocida toxin (PMT) to various proteases was investigated. PMT at a toxin to protease molar ratio of 1 : 1 was resistant to 8 of the 11 proteases tested after one hour. With longer incubation, PMT remained resistant to 7 proteases, and this correlated with a retention of biological activity, indicating that PMT might not require proteolytic cleavage at least until it bound to a cell receptor. Previous evidence had suggested that PMT is processed in the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…PMT has previously been shown to be highly resistant to most proteases at neutral pH (46). One protease, Asp-N, was found to cleave PMT at pH 7, producing three fragments of ca.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…PMT has previously been shown to be highly resistant to most proteases at neutral pH (46). One protease, Asp-N, was found to cleave PMT at pH 7, producing three fragments of ca.…”
Section: Resultsmentioning
confidence: 99%
“…One protease, Asp-N, was found to cleave PMT at pH 7, producing three fragments of ca. 90, 87, and 55 kDa (46). Amino-terminal sequencing of these fragments showed that the toxin was cleaved between residues 473 and 474, and between 509 and 510.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The toxin is passively released upon bacterial lysis and is believed to be actively taken up by host cells via receptor -mediated endocytosis by binding to a ganglioside cell surface receptor (Pettit et al 1993 ). The N -terminal receptor -binding domain is then proteolytically cleaved under low pH conditions (Smyth et al 1995 ), exposing the translocation domain, which allows uptake into the cytoplasm . Here the catalytic C -terminal portion of the protein activates two heterotrimeric G proteins, G α q and G α 12/13 , which in turn affect a number of host signal transduction pathways ).…”
Section: Pmtmentioning
confidence: 99%
“…The translocation depends on a putative translocation T-domain, consisting of two predicted hydrophobic helices (residues 402-423 and 437-457) linked by a peptide loop (residues 424-436). It is proposed that acidification induces a structural change in the toxin, which was previously observed utilising circular dichroism and measuring susceptibility to proteases (Smyth et al 1995(Smyth et al , 1999. This structural change exposes the T-domain, allowing it to insert into the vesicular membrane.…”
Section: Uptake Into Eukaryotic Cellsmentioning
confidence: 96%